2017
DOI: 10.1007/s40272-017-0248-y
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Safety, Efficacy and Mechanisms of Delivery of Nasal Oxytocin in Children: Therapeutic Potential for Autism and Prader-Willi Syndrome, and Recommendations for Future Research

Abstract: In this article, we conduct a comprehensive review of existing evidence for the safety and therapeutic potential of intranasal oxytocin in pediatric populations. Unique considerations for dosing and delivery of oxytocin to the nasal passageway in pediatric populations and methods to promote adherence are reviewed. Intranasal oxytocin has been administered to 261 children in three open-label studies and eight randomized controlled trials. To date, the only published results in pediatric populations have focused… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 90 publications
1
46
0
Order By: Relevance
“…Synthetic OT is used widely in clinical settings for inducing and accelerating labor. Because of its ability to modulate a wide variety of social behaviors (Lee et al, 2009), OT is currently being evaluated for its clinical use in disorders with a social component, such as autism spectrum disorder and schizophrenia (Bakermans-Kranenburg and van Ijzendoorn, 2013;Feifel et al, 2016;DeMayo et al, 2017;Parker et al, 2017). Considerable effort has been invested in engineering OT analogs and formulations for potential therapeutic use and to extend understanding of OT actions, particularly central nervous system and behavioral effects (Manning et al, 2012;Busnelli et al, 2013;Muttenthaler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic OT is used widely in clinical settings for inducing and accelerating labor. Because of its ability to modulate a wide variety of social behaviors (Lee et al, 2009), OT is currently being evaluated for its clinical use in disorders with a social component, such as autism spectrum disorder and schizophrenia (Bakermans-Kranenburg and van Ijzendoorn, 2013;Feifel et al, 2016;DeMayo et al, 2017;Parker et al, 2017). Considerable effort has been invested in engineering OT analogs and formulations for potential therapeutic use and to extend understanding of OT actions, particularly central nervous system and behavioral effects (Manning et al, 2012;Busnelli et al, 2013;Muttenthaler et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…After 6 months of cellular therapy, improvements in concentration, sitting tolerance, attention, sleep, eye contact, social interactions, and memory were reported, as measured by ISAA, CARS, and Functional Independence Measure scores before and after cellular treatment. Six months posttherapy, 18 F-FDG PET scan showed improvements in brain hypometabolism.…”
Section: Stem Cells and Autism: Clinical Trialsmentioning
confidence: 98%
“… 17 Hormonal therapies with oxytocyin have also shown some promises in improving central ASD symptoms. 18 The use of vitamins, herbals, essential oils, and nutritional supplements 19 , 20 and conventional therapies have some effect in symptomatic improvement in ASD, though additional studies are needed to confirm these benefits. Developing novel therapies may prove to be the ultimate intervention for sustained improvement of symptoms in ASD.…”
Section: Autism Spectrum Disorders (Asds)mentioning
confidence: 99%
See 1 more Smart Citation
“…A confluence of recent evidence has demonstrated that OT nasal spray enhances social cognition by improving social recognition, encoding of social memories, retrieval of social cues, and accurate and positive appraisal of social information at various levels of processing (Guastella & MacLeod, ), including in young children with autism (Yatawara, Einfeld, Hickie, Davenport, & Guastella, ). While there is consistent evidence suggesting the short‐term safety of oxytocin administration to paediatric populations (DeMayo, Song, Hickie, & Guastella, ), recent commentaries on the use of intranasal OT have argued for caution in regards to possible longer term effects on social development, particularly when exogenous administration is provided very early in life (Miller, ). Oxytocin is able to cross the placenta, and it has been argued that the transmission of exogenous OT to the foetus in this early phase of development may cause deleterious impacts on long‐term social and emotional development (Carter, ).…”
Section: Introductionmentioning
confidence: 99%